<u>Answer:</u>
The equation through (-3, -2) and perpendicular to y = x – 1 is y = -x -5 and option c is correct.
<u>Solution:</u>
Given, line equation is y = x – 1 ⇒ x – y – 1 = 0. And a point is (-3, -2)
We have to find the line equation which is perpendicular to above given line and passing through the given point.
Now, let us find the slope of the given line equation.
![\text { Slope }=\frac{-x \text { coefficient }}{y \text { coefficient }}=\frac{-1}{-1}=1](https://tex.z-dn.net/?f=%5Ctext%20%7B%20Slope%20%7D%3D%5Cfrac%7B-x%20%5Ctext%20%7B%20coefficient%20%7D%7D%7By%20%5Ctext%20%7B%20coefficient%20%7D%7D%3D%5Cfrac%7B-1%7D%7B-1%7D%3D1)
We know that, <em>product of slopes of perpendicular lines is -1.
</em>
So, 1
slope of perpendicular line = -1
slope of perpendicular line = -1
Now let us write point slope form for our required line.
![\mathrm{y}-\mathrm{y}_{1}=\mathrm{m}\left(\mathrm{x}-\mathrm{x}_{1}\right)](https://tex.z-dn.net/?f=%5Cmathrm%7By%7D-%5Cmathrm%7By%7D_%7B1%7D%3D%5Cmathrm%7Bm%7D%5Cleft%28%5Cmathrm%7Bx%7D-%5Cmathrm%7Bx%7D_%7B1%7D%5Cright%29)
y – (-2) = -1(x – (-3))
y + 2 = -1(x + 3)
y + 2 = -x – 3
x + y + 2 + 3 = 0
x + y + 5 = 0
y = -x -5
Hence the equation through (-3, -2) and perpendicular to y = x – 1 is y = -x -5 and option c is correct.
Answer
Step-by-step explanation:
I am not an artist so
Answer: this is the right answer Graph A represents j(x). The y-intercepts for f(x) and g(x) can be 1 and 3. And The rate of change of the sum of f(x) and g(x) is greater than that of either function. your welcome
Step-by-step explanation:
Answer:23
Step-by-step explanation:
Answer:
4 * 14 = 56
Step-by-step explanation:
56/2 = 28
28/2 = 14
14/2 = 7
7/7 = 1
56 = 2 * 2 * 2 * 7
56 = (2 * 2) * (2 * 7)
56 = 4 * 14